Trophic status of the Bandar Kayangan Lembah Sari Reservoir, Rumbai Pesisir Sub-district, Pekanbaru Based on Nitrate and Phosphate Concentration - Berton Panjaitan; Asmika Harnalin Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
as a basis to determine the trophic status of the waters. A research aims tounderstand the trophic status of the waters of the Bandar Kayangan Lembah Sarireservoir was conducted in Mach-April 2016.There were 4 stations, namely St 1 (in theinlet from Ambang River), St 2 (in the inlet from Merbau River), St3 (in the middle ofthe lake) and St 4 (in the dam). Samplings were conducted 3 times, once/ week. Watersamples were taken from the water surface.Results shown that nitrate concentration was ranged from 0.075 – 0.096 mg/L,phosphate from 0.208 – 0.293 mg/L, temperature 31-32°C, transparency 56.8 – 60.2 cm,depth 219.3 – 378.7 cm, velocity0.25 – 0.40 cm/s, pH was4, dissolved oxygen (DO)5.38 – 8.31mg/L. Based on nitrate concentration, the trophic status of the BandarKayangan Lembah Sari reservoir was categorized as oligotrophic, whereas based onphosphate concentration, it can be categorized as eutrophic.Keyword: trophic status, nitrate, phosphate, Bandar Kayangan Lembah Sari lake